1987
DOI: 10.1177/016173468700900304
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Ultrasonic Nonlinear Parameter B/A on Fat

Abstract: This study deals with the relationship between the magnitude of acoustic nonlinearity, sound speed of tissues and the amount of fat present in them. A two-component model, i.e., nonfat and fat, has been assumed and equations that relate the nonlinear parameter (B/A) of a medium to the properties of its components have been derived for two cases. In the first case, the density and sound speed are the same for the two components; B/A is a linear function of fat concentration. To represent this case, mixtures of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…23 In experimental settings, it is has been shown that the SV depends on the fat content of the tissue and is slower in fat compared to water and human tissue. [24][25][26] In this study, all patients with cirrhosis who were missed by the SV measurements were not only obese but also had a lower SV in the liver compared to the cutoff of value of 1589 m/s and the mean SV value for the population with cirrhosis.…”
Section: Discussionmentioning
confidence: 85%
“…23 In experimental settings, it is has been shown that the SV depends on the fat content of the tissue and is slower in fat compared to water and human tissue. [24][25][26] In this study, all patients with cirrhosis who were missed by the SV measurements were not only obese but also had a lower SV in the liver compared to the cutoff of value of 1589 m/s and the mean SV value for the population with cirrhosis.…”
Section: Discussionmentioning
confidence: 85%
“…It is seen that the B/A value due to ribonuclease At decreases as it is denatured, which supports the result obtained by SDS denaturation. Errabolu et al (1987) have also observed the lower B/A value associated with denatured protein, in studies of the dependence of the B/A parameter on the different constituents of fatty tissues, by decomposing the fat tissues into three components, viz., water, oily residue: and solid residue. They pointed out that the solid residue, one of the dehydration products composed largely of denatured proteins, exhibits significantly lower B/A values.…”
Section: Effects Of Protein Tertiary and Secondary Structurementioning
confidence: 96%